Recent applications of starch derivatives in nanodrug delivery - Rodrigues, Asha; Emeje, Martins (Carbohydrate Polymers, 2012)
Starch has found use in industries as diverse as food, textiles, cosmetics, plastics, adhesives, paper, and pharmaceuticals. From a pharmaceutical standpoint, starch finds its value in solid-oral dosage forms, where it has been used as a binder, diluent, and disintegrant. However, only recently has the use of starch in nanotechnology started to make significant advances in biomedical applications, including newer drug delivery techniques. There has been a considerable effort to develop biodegradable nanoparticles as effective drug delivery systems. Being cheap, non-toxic, renewable, biodegradable and compatible with many other materials for industrial applications, starch is attracting the interest of drug delivery scientists. We have put together in a short and concise format, recent applications of starch derivatives in the emerging field of nanodrug delivery with the conclusion that a lot still needs to be done. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Applications; nanotechnology; Starch